What leads to direct epoxidation? an exhaustive DFT investigation of electrophilic oxygen mediated epoxidation of ethylene on Ag(100) - Nair, Aathira; Joshi, Kavita (Computational Materials Science, 2024)
Extensive research has contributed to a better understanding of the commercially important epoxidation reaction. Selectivity, a crucial aspect of this reaction, has received significant attention in both experimental and theoretical investigations. However, a consensus regarding the role of electrophilic oxygen in epoxidation is yet to be reached. The present study is a theoretical examination of the prerequisites necessary for direct epoxidation to occur on the Ag(100) surface, at varied monolayer concentrations. Additionally, the study investigates the characteristics of various oxygen species interacting with ethylene to promote the direct epoxidation pathway. Based on the effective charges and projected density of states (pDOS) analysis, three oxygen variants were identified on the Ag(100) surface: atomic oxygen, dissociatively adsorbed molecular oxygen, and O 3 . The investigation reveals that all oxygen species, despite their physical and electronic differences, are electrophilic and undergo direct epoxidation. This work provides insights into the complex nature of epoxidation reaction and discusses electronic factors influencing the selective oxidation route on different Ag-O complexes.
Keywords: Ag(100); DFT; Direct epoxidation; Electrophilic oxygen; Ethylene Oxide (EtO); OMC